Social anxiety, fear of negative evaluation and the detection of negative emotion in others. - Winton, E; Clark, D; Edelmann, R (1995)
The present study sought to investigate whether social anxiety is associated with enhanced ability to detect negative emotion in others. Subjects scoring high and low on Fear of Negative Evaluation (FNE) performed two tasks before and after a social threat induction. The first task involved identifying the affect (negative vs neutral) in briefly presented (60 msec) slides of faces. The second involved rating the overall emotion conveyed in brief video clips of an actor and detecting discrepancies in the affect conveyed by the visual and auditory channels of the video. Overall the results suggest that high social anxiety subjects have a bias towards identifying others' emotional expressions as negative in the absence of an enhanced ability to discriminate between different emotional states in others. Implications and limitations of the results are discussed.